2016
DOI: 10.1039/c6ra09195d
|View full text |Cite
|
Sign up to set email alerts
|

The xylene sensing performance of WO3 decorated anatase TiO2 nanoparticles as a sensing material for a gas sensor at a low operating temperature

Abstract: Here, the pristine and WO3 decorated TiO2 nanoparticles were synthesized by a one-step hydrothermal without the use of a surfactant or template, and used to fabricate gas sensors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 53 publications
(17 citation statements)
references
References 63 publications
0
17
0
Order By: Relevance
“…S4(a) and (b), respectively. The peak with lower binding energy around 530 eV is associated to the oxygen atom in the crystal lattice, while the peak with higher binding energy is assigned to the absorbed oxygen ion61. It proves that there surely exist the oxygen related defects including the oxygen vacancy.…”
Section: Resultsmentioning
confidence: 87%
“…S4(a) and (b), respectively. The peak with lower binding energy around 530 eV is associated to the oxygen atom in the crystal lattice, while the peak with higher binding energy is assigned to the absorbed oxygen ion61. It proves that there surely exist the oxygen related defects including the oxygen vacancy.…”
Section: Resultsmentioning
confidence: 87%
“…Perillo et al [56] reported that the sensitivity of TiO 2 nanotubes on Si wafer-based sensor towards CO gas is 0.016. Such relatively low sensitivities may not meet the requirement of practical application [57] since a high working range of CO concentrations (> 100 ppm) is obtained by those previous studies. A quiet higher sensitivity and a lower working range of concentrations (< 100 ppm) were obtained by other TiO 2 nanotube-based CO gas sensors, as reported by Gönüllü et al [58] and Kim et al [59].…”
Section: Gas Sensing Studymentioning
confidence: 73%
“…Similar to microstructure-based volatile hydrocarbon vapors quantification (example: Sn 2+ doped NiO microspheres in Xylene detection with sub-ppm LOD) [ [390][391][392][393][394][395][396][397]. Wherein, Ag/Bi 2 O 3 nanocomposite and Graphene/SnO 2 NPs nanocomposite were found to perform remarkably in terms of their operation temperature (at room temperature) [394,397].…”
Section: Volatile Hydrocarbons Detection By Distinct Nanostructuresmentioning
confidence: 84%
“…Similar to microstructure-based volatile hydrocarbon vapors quantification (example: Sn 2+ doped NiO microspheres in Xylene detection with sub-ppm LOD) [ 389 ], nanocomposites, such as Pd/PdO/S-SnO 2 nanocomposite film, rGO/Co 3 O 4 nanocomposite, WO 3 decorated TiO 2 NPs nanocomposite, BGQD/Ag–LaFeO 3 nanocomposite, Ag/Bi 2 O 3 nanocomposite, AgO loaded LaFeO 3 nanocomposite, CuO NPs-Ti 3 C 2 Tx MXene nanocomposite, and Graphene/SnO 2 NPs nanocomposite were effectively applied in the detection of hydrocarbons as detailed in Table 5 [ 390 , 391 , 392 , 393 , 394 , 395 , 396 , 397 ]. Wherein, Ag/Bi 2 O 3 nanocomposite and Graphene/SnO 2 NPs nanocomposite were found to perform remarkably in terms of their operation temperature (at room temperature) [ 394 , 397 ].…”
Section: Volatile Hydrocarbons Detection By Distinct Nanostructurementioning
confidence: 99%